2020
DOI: 10.3390/vaccines8010075
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies Between Protocols of Immunization Targeting Internationally Adopted Children in Western Countries

Abstract: The immunization status of Internationally Adopted Children (IAC) newly arrived in the adoptive country require a timely assessment and completion of necessary vaccinations. In fact, due to their frequent suboptimal immunization status, IAC are at high risk for vaccine preventable diseases (VPDs). Comparative analysis of immunization protocols adopted in European countries, United States, and Canada disclosed different approaches to the immunization of these children. In order to guarantee the continuity of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Moreover, another multicenter study conducted ina Northern (Liguria) and a Southern (Apulia) Italian region found poor knowledge but good attitudes among undergraduates about HPV vaccination [ 20 ]. A review conducted on immunization protocols of IAC in Western countries demonstrated substantially different approaches that should be corrected [ 21 ]. Glatman-Freedman et al analyzed the variation in the vaccine effectiveness (VE) of influenza vaccination in Israel during the 2018/2019 season according to different clades of influenza A (H3N2) virus [ 22 ], and Barbara et al observed a substantial increase of vaccination adherence among HCWs of the Catholic UH of Rome, Italy, due to evidence-based promoting strategies [ 23 ].…”
Section: Manuscripts Included In the Special Issuementioning
confidence: 99%
“…Moreover, another multicenter study conducted ina Northern (Liguria) and a Southern (Apulia) Italian region found poor knowledge but good attitudes among undergraduates about HPV vaccination [ 20 ]. A review conducted on immunization protocols of IAC in Western countries demonstrated substantially different approaches that should be corrected [ 21 ]. Glatman-Freedman et al analyzed the variation in the vaccine effectiveness (VE) of influenza vaccination in Israel during the 2018/2019 season according to different clades of influenza A (H3N2) virus [ 22 ], and Barbara et al observed a substantial increase of vaccination adherence among HCWs of the Catholic UH of Rome, Italy, due to evidence-based promoting strategies [ 23 ].…”
Section: Manuscripts Included In the Special Issuementioning
confidence: 99%
“…The management of IAC lacks evidence-based guidelines and fails to cover the entirety of the conditions that might affect the population [ 14 ]. Eosinophilia can be linked to parasitosis [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Testing for HBcAb makes the HBV-assessment more complete. Positive HBcAb and negative HBsAg can be detected in four different conditions: acute HBV infection, low levels of HBsAb in the serum that are not detectable by serotesting, susceptibility to HBV because of a false positive HBcAb, and undetectable level of HBsAg present in serum when the child is chronically infected [32].…”
Section: Introductionmentioning
confidence: 99%